An Analysis of Learning Motivation of First-Year Psychology Students at the University of Jambi - Vadya, Amanda Putri; Calista, Naura Aurelia; Liviany, Siti Octazahrah; Rahim, Beny; Ilham, Muhammad; Periantalo, Jelpa (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: Learning motivation is one of the key factors that influence students' academic achievement. This study aims to examine the level of learning motivation of level 1 Psychology students at Jambi University based on gender. Research Methods: This study uses a quantitative method with a survey approach, where motivation measurement is carried out using a Likert scale that has been tested for validity and reliability. This study uses reverse scoring that some item has a negative composition. The sample in this study amounted to 115 students selected through purposive sampling technique. Finding/Results: The results showed that the majority of students had a level of learning motivation in the very good and good categories. Then the level of motivation in female students is higher than male students. Intrinsic factors, namely talent, have a higher contribution than other factors, then extrinsic factors, namely the world of work, have a higher contribution than other factors. Conclusion: By considering these factors, it is hoped that educational institutions will be able to develop academic coaching that can support learning motivation factors, especially talent and world of work factors so that students are able to set clear and sustainable learning goals.